GE ecomagination - Bagley, Constance E.; Dhar, Ravi; Morton, Fiona M. Scott (London : SAGE Publications Ltd, 2017)
The 1990s ushered in a new era of doing business in a global economy. Reports by the United Nations Intergovernmental Panel on Climate Change had concluded that humankind was likely playing a role in global warming, and the Kyoto Protocol had established mandatory targets for certain developed countries to reduce their greenhouse gas (GHG) emissions by 2012.The United States did not sign the Kyoto Protocol and has not adopted any mandatory climate change regulations to date. However, the IPCCs findings have led to a growing belief among Americans that humans are in fact contributing to global warming. As a result, America has experienced a shift in consumer behavior, with consumers now demanding more environmentally friendly choices for products ranging from automobiles to household cleaners.
Originally published: Bagley, C. E., Dhar, R., & Scott Morton, F. M. (2011). 11-032. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/ge-ecomagination/.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Canada. -- Case studies; Climatic changes -- Government policy -- United States -- Case studies; Greenhouse gas mitigation -- Government policy -- United States -- Case studies; Environmental policy -- United States -- Case studies